Satisfaction with life and character strengths of non-religious and religious people: it’s practicing one’s religion that makes the difference - Berthold, Anne; Ruch, Willibald (Frontiers in Psychology, 2014)
According to systematic reviews, religious beliefs and practices are related to higher life satisfaction, happiness, and positive affect (Koenig & Larson, 2001). The present research extends previous findings by comparing satisfaction with life and character strengths of nonreligious people, religious people, who practice their religion and people that have a religious affiliation but do not practice their religion. We assessed life satisfaction (SWLS), character strengths (VIA-IS) and the orientations to happiness (OTH) in a sample of N=20538 participants. People with a religious affiliation that also practice their religion were found to be more satisfied with their life and scored higher on life of meaning than those who do not practice their religion and than nonreligious people. Also religious people who practice their religion differed significantly from those who do not practice their religion and nonreligious people regarding several character strengths; they scored higher on kindness, love, gratitude, hope, forgiveness, and on spirituality. There were no substantial differences between people who had no religious affiliation and those with a religious affiliation that do not practice their religion (all ηp2s < .009). Altogether, the present findings suggest that people profit from a religious affiliation if they also actively practice their religion.